2019
DOI: 10.1002/aur.2094
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a hyperarousal hypothesis of insomnia in adults with autism spectrum disorder

Abstract: This study aimed to investigate the relationship between sleep, psychopathology (anxiety, depression and presleep arousal) symptoms, and cortisol in adults with autism spectrum disorder (ASD). The sample composed of 29 adults with ASD (51.7% males) and 29 control adults (51.7% males) aged 21-44 years. Thirteen adults with ASD were medicated for a comorbid diagnosis of anxiety and/or depression (ASD-Med), while the remaining 16 adults with ASD were not medicated for such diagnoses (ASD-Only). Participants compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Adults with ASD have dampened cortisol secretion and subjective somatic physiological arousal, associated with increased sleep onset latency, poorer sleep efficiency, and increased waking after sleep onset. This corroborates the hypothesis that dysregulation of the SNS-HPA is a key mechanism underlying phenotypic expression of ASD (Baker et al, 2019).…”
Section: Parent–infant Biobehavioral Synchrony Optimizes Reciprocity supporting
confidence: 90%
“…Adults with ASD have dampened cortisol secretion and subjective somatic physiological arousal, associated with increased sleep onset latency, poorer sleep efficiency, and increased waking after sleep onset. This corroborates the hypothesis that dysregulation of the SNS-HPA is a key mechanism underlying phenotypic expression of ASD (Baker et al, 2019).…”
Section: Parent–infant Biobehavioral Synchrony Optimizes Reciprocity supporting
confidence: 90%
“…Previous research has identified that the hyperarousal is associated with elevated levels of cortisol in insomnia patients (Vgontzas et al 2001;Rodenbeck et al 2002). Similar findings have been reported in the ASD population, whereby individuals with ASD experiencing sleep problem such as insomnia report elevated rates of cortisol compared with controls (Richdale & Prior 1992;Corbett et al 2008;Baker et al 2019). This elevation in cortisol provides support for a hyperarousal hypothesis of insomnia for individuals with ASD.…”
Section: Discussionmentioning
confidence: 58%
“…2008; Baker et al . 2019). This elevation in cortisol provides support for a hyperarousal hypothesis of insomnia for individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence also indicates a high rate of physical health issues in about 40%–60% of autistic adults including allergy, cardiovascular disease, obesity, neurological conditions, gastrointestinal disorders and sleep disorders (Croen et al, 2015; Jones et al, 2016). Autistic adults have more frequent sleeping difficulties than comparison groups (Limoges et al, 2005; Tani et al, 2003), and poor sleep is related to poor mental health (Baker et al, 2019; Tani et al, 2003) and pre-sleep arousal (Baker et al, 2019). Symptoms associated with insomnia and circadian sleep–wake disorders appear most common (Baker & Richdale, 2015, 2017; Hare et al, 2006).…”
mentioning
confidence: 99%